Utilizing Design Thinking to Enhance Wellbeing in Interdisciplinary Courses: A Positive Social Psychology Approach - Areej ElSayary (Journal of Systemics, Cybernetics and Informatics)

(untitled)
Design thinking is considered to be a positive social psychology intervention. Students who practice using the design thinking process during their coursework will most likely solve personal problems that improve their well-being. This study investigates the impact of using the design thinking process in interdisciplinary courses to enhance students' well-being through developing mindsets that enable them to solve their problems and set personal goals unconsciously. A modified PERMA-PH model is used to guide this study. The PERMA included Positive Emotions, Negative Emotions, Engagement, Relationship, Meaning and Purpose, and Accomplishments, the "PH" (future plans and health) was added to the PE to ensure continuity of students' capability in improving their well-being. The participants (n=38) were undergraduate female students (preservice teachers) at a Federal University in the United Arab Emirates (UAE). A sequential mixed-method approach using quantitative and qualitative data was used. An online survey with closed-ended items was adopted to collect data from participants. The qualitative data were collected using semi-structured interviews with six students. The study's results reveal that students improved their well-being when engaged in the design thinking process during their reflection in the interdisciplinary courses, and expectations of continuing to improve their well-being occurred.